Allergic asthma in children: Inherited, transmitted or both? (The transmission of periodontopathic bacteria concept) - Seno Pradopo; Haryono Utomo (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: In theory, allergic diseases including asthma, was the resultof exposure to a transmissible agent and do not depend on early infection which is said to make children more allergy-resistant. This seems, to be a direct contradiction to the hygiene hypothesis, since epidemiologic evidence can be cited in this theory's support. The fact that nearly all childrenwith asthma are allergic, but only a small proportion of allergicchildren have asthma, at least raises the possibility that someadditional factor is involved. That this additional factor might be a transmissible agent is also suggested by the similarity between the gross epidemiologic patterns of children with paralyticpoliomyelitis in the 1950s and children with asthma currently. Purpose: The purpose of this study was to reveal the possible relationship between the transmissions of allergic asthma and periodontopathic bacteria. Reviews: Recent researches showed that periodontopathic bacteria are transmissible from mother and caregivers to infants. In addition, a collaborated research that was conducted by dental practitioners and pediatricians revealed that Gram-negative bacteria were significantly predominant (p = 0.001) in uncontrolled allergic asthmatic children compared to well-controlled ones. Nevertheless, how does these two phenomenon related was still uncertain. Literatures showed that periodontopathic bacteria modulates host immune response and sometimes caused disadvantageous effect to allergic asthma. Conclusion: According to the ability of periodontopathic bacteria and its components to stimulate immunocompetent cells, it is possible that they are able to modify host-immune response which tends to increase allergic asthma symptoms.